Lily and the duke - Hardt, Helen (Hardt, Helen. Sex and the season, 2015)
Lady Lily Jameson is thrilled to attend a house party given by Daniel Farnsworth, the Duke of Lybrook, but not because he's the most eligible bachelor in the peerage. Her only interest is his famous art collection which reputedly includes a painting by her favorite artist, Jan Vermeer. Daniel, duke only by virtue of the untimely deaths of his father and older brother, wants nothing to do with his new duties. He'd rather continue his rakish ways. When he finds the lovely Lily sneaking around the property in search of his art collection, sparks fly. Despite her father's wishes, Lily has no intention of marrying. She wants to travel the world to gain real life inspiration for her painting and writing. And what could be better worldly experience than a passionate affair with the notorious Duke of Lybrook? But circumstances may change the game and the players ... and danger lurks as well.